Clinical experience in the evaluation of 30 patients with a prior diagnosis of FG syndrome. Issue 1 (19th September 2008) - Lyons, M J; Graham, J M; Neri, G; Hunter, A G W; Clark, R D; Rogers, R C; Moscarda, M; Boccuto, L; Simensen, R; Dodd, J; Robertson, S; DuPont, B R; et al.
Abstract : Background: FG syndrome (FGS) is an X-linked disorder characterised by mental retardation, hypotonia, particular dysmorphic facial features, broad thumbs and halluces, anal anomalies, constipation, and abnormalities of the corpus callosum. A behavioural phenotype of hyperactivity, affability, and excessive talkativeness is very frequent. The spectrum of clinical findings attributed to FGS has widened considerably since the initial description of the syndrome by Opitz and Kaveggia in 1974 and has resulted in clinical variability and genetic heterogeneity. In 2007, a recurrent R961W mutation in the MED12 gene at Xq13 was found to cause FGS in six families, including the original family described by Opitz and Kaveggia. The phenotype was highly consistent in all the R961W positive patients. Methods: In order to determine the prevalence of MED12 mutations in patients clinically diagnosed with FGS and to clarify the phenotypic spectrum of FGS, 30 individuals diagnosed previously with FGS were evaluated clinically and by MED12 sequencing. Results: The R961W mutation was identified in the only patient who had the typical phenotype previously associated with this mutation. The remaining 29 patients displayed a wide variety of features and were shown to be negative for mutations in the entire MED12 gene. A definite or possible alternative diagnosis was identified in 10 of these patients. Conclusion: This report illustrates the difficulty in making a clinical diagnosis of FGS given the broad spectrum of signs and symptoms that have been attributed to the syndrome. Individuals with a phenotype consistent with FGS require a thorough genetic evaluation including MED12 mutation analysis. Further genetic testing should be considered in those who test negative for a MED12 mutation to search for an alternative diagnosis.